1997
DOI: 10.1021/om9605995
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effects in Asymmetric Catalysis. Synthesis and Structure of Model Rhodium Complexes Containing Ferrocenyl Ligands for Use in the Hydroboration Reaction

Abstract: A series of new rhodium complexes with chiral ferrocenyl chelating ligands containing a tertiary phosphine and a pyrazole moiety have been obtained in good yields from the reaction of the corresponding P,N ligand (1a − p) with [Rh(1,5-COD)2]BF4, [Rh(CO)2Cl]2, and [Rh(COE)2Cl]2. The electronic influence of the P,N ligands has been evaluated by the measurement of the carbonyl stretching vibration in the compounds 5a − p. Qualitative trend correlations between ν(CO) values for such complexes and the enantioselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 21 publications
8
41
0
1
Order By: Relevance
“…Several structural elements are present on the PPF scaffold that could contribute to its successful application in these reactions (51)(52)(53). PPF has elements of central and planar chirality as well as two phosphine atoms that differ both sterically and electronically.…”
Section: Ligand Studies: Variations On the Josiphos Template And Othementioning
confidence: 99%
“…Several structural elements are present on the PPF scaffold that could contribute to its successful application in these reactions (51)(52)(53). PPF has elements of central and planar chirality as well as two phosphine atoms that differ both sterically and electronically.…”
Section: Ligand Studies: Variations On the Josiphos Template And Othementioning
confidence: 99%
“…Furthermore, there is considerable current interest in hybrid P/N ligands and a search in the Cambridge Structure Database revealed that although a vast number of Groups 9-10 complexes with nitrogen and phosphorus ligands have been characterised structurally, only a relatively small number of Pd(II) cations and Rh(I) cations [54][55][56][57][58][59][60][61][62][63][64][65] containing bidentate N(sp 2 )-P(sp 3 ) donors are reported. Since bulky substituents at the aryl groups of N(sp 2 ) donors have been found to strongly influence the catalytic activity and selectivity of Group 10 complexes [66], it is surprising that no Rh(I) complexes of ligands combining tertiary phosphine donors and (sp 2 )N-aryl donors with bulky ortho substituents have been structurally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium complexes (1 mol%) prepared in situ from [Rh(COD) 2 ]BF 4 and the respective ligands (70 -73) were employed in the enantioselective hydroborationoxidation of styrene (28) ( Table 3.3 ) [63,64] .…”
Section: Selectivity Of Metal-catalyzed Hydroboration 75mentioning
confidence: 99%